Combined Left Central Retinal Artery Occlusion and Bilateral Anterior Ischemic Optic Neuritis: A Rare Presentation of Giant Cell Arteritis - Anne D. D. Joseph; Jebananthy Anandaselvam Pradeepan; Thirunavukarasu Kumanan; Muthusamy Malaravan (Case Reports in Rheumatology, 2019)
Giant cell arteritis, a large vessel vasculitis is characterized by headache, visual impairment, constitutional symptoms, and increased inflammatory markers. Visual involvement in giant cell arteritis ranges from amaurosis fugax to permanent visual loss, and extensive bilateral visual impairment is a rare presentation. We hereby report a case of combined left central retinal artery occlusion and bilateral anterior ischemic optic neuritis in a patient who poorly responded to standard corticosteroid therapy.